Synthesis and Characterization of ZnO-Nanocomposites by Utilizing Aloe Vera Leaf Gel and Extract of Terminalia arjuna Nuts and Exploring Their Antibacterial Potency - Amara Dar; Rabia Rehman; Warda Zaheer; Umer Shafique; Jamil Anwar (Journal of Chemistry)
Nanotechnology has found vast applications in everyday life. Use of plant extract in the synthesis of nanocomposites produces relatively less toxic and environment-friendly materials. The present study deals with the synthesis of zinc oxide nanocomposite using gel from leaves of Aloe vera (black Aloe vera (BAV) and white Aloe vera (WAV)) and extract from powder of nuts of Terminalia arjuna. Synthesized nanocomposites were then characterized by using SEM, FTIR, and UV-Vis techniques. Disc diffusion method was opted to inquire the antimicrobial ability of nanocomposites against different bacterial strains such as Escherichia coli (−) and Burkholderia stabilis (+). ZnO-BAV possessed good antimicrobial potential against both selected strains as proved from zone of inhibitions. However, ZnO-WAV and ZnO-N showed potential against E. coli and no response for B. stabilis.